1980
DOI: 10.1039/p29800000647
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies. Part 58. The formation and reactions of some aliphatic radical-cations in aqueous solution

Abstract: Evidence is presented that reaction of C12-' with vinyl ethers proceeds via the formation of the radical-cations of the parent compounds. These species are not directly detectable by e.s.r., but the spectra of radicals formed in one or more of three further reactions have been characterized. These reactions are hydration, addition to the parent molecule, and deprotonation [e.g., CH,=CHOEt+' (from ethyl vinyl ether) yields the hydroxylated radicals*CH(OEt)-CH,OH and *CH,CH(OH)OEt and the ' dimer ' radical -CH(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 6 publications
5
15
0
Order By: Relevance
“…The neat liquid sample gave similar results for A µ (see Table 1). Comparison with ESR data [38][39][40][41] and an earlier muon spectroscopic study 23 indicates that the stronger signal (smaller muon hfc) is due to radical 5 and the weaker signal is from 4. This assignment is supported by our DFT calculations, which show that 5 is more stable than 4, as might be expected from the enhanced spin delocalization over the allylic structure.…”
Section: Resultsmentioning
confidence: 99%
“…The neat liquid sample gave similar results for A µ (see Table 1). Comparison with ESR data [38][39][40][41] and an earlier muon spectroscopic study 23 indicates that the stronger signal (smaller muon hfc) is due to radical 5 and the weaker signal is from 4. This assignment is supported by our DFT calculations, which show that 5 is more stable than 4, as might be expected from the enhanced spin delocalization over the allylic structure.…”
Section: Resultsmentioning
confidence: 99%
“…Gilbert et al (13) have reported formation of radical cations from the reaction of C12; with alkoxy-substituted olefins. In the current studies, an alternative mechanism leading to hydroxy spin adducts, involving nitrone radical cations (14) rather than intermediate chlorine spin adducts of PBN, cannot be ruled out.…”
Section: Candc(o)n(o )C4h9mentioning
confidence: 99%
“…The spectrum of the DHP radical simulated with the set of hfs splitting constants given in Table 2 is shown in Figure 3(c). The same DHP radical was also generated chemically [22,23] and photochemically; [24] the experimental values of the hfs splitting constants are also summarized in Table 2.…”
Section: Dihydropyryl Radicalmentioning
confidence: 99%